Anticoagulation and antiplatelet therapy in short bowel syndrome: A systematic review - Carolyn Mercer; Anna Crawford; Susan Shapiro; Philip J. Allan; Tim Ambrose (Intestinal Failure)
Background: Short bowel syndrome (SBS) is one cause of intestinal insufficiency or failure. Drug therapy may be difficult in this patient group at least in part due to abnormalities in anatomy or surface area for absorption. Anticoagulation may be indicated due to the underlying cause of SBS or to treat complications of parenteral support. Aims: To review the literature on the use of anticoagulation and antiplatelet agents in SBS. Methods: Systematic literature search in MEDLINE, EMBASE and the Cochrane library for studies pertaining to SBS, anticoagulants and antiplatelets to 22nd February 2024. Results: 24 of 725 screened articles met the eligibility criteria. The majority were case reports or series with no randomised controlled trials. Warfarin was the most studied anticoagulant with adequate anticoagulation with gut lengths as short as 12 cm. Rivaroxaban was the most studied DOAC with target plasma concentrations achieved with as little as 30 cm intestine. Apixaban was studied in one case with target plasma concentrations reached and no recurrent thrombosis or bleeding events. Dabigatran was not shown to reliably achieve target plasma concentrations. Minimal data was available on antiplatelet agents in short bowel syndrome with no long term clinical outcomes reported. Conclusions: The literature is largely limited to case reports and series. Warfarin is the most widely studied anticoagulant in SBS and is effective. Absorption of rivaroxaban and, probably, apixaban is adequate in SBS but longer term studies on clinical outcomes are needed. Insufficient data is available to make firm recommendations for antiplatelet therapy.